Pathogen Detection on Inanimate Surfaces in Healthcare Institutions: Phenotype and Genotype Detection Methods - Sabina Fijan; Urška Rozman; Sonja Šostar Turk (Medicine and Medical Research: New Perspectives Vol. 12, 2024)
Aims: The persistence and transmission of microorganisms, especially in hospitals and other healthcare-associated facilities, are critical concerns in addressing healthcare-associated infections (HCAI). This comprehensive chapter addresses various facets of environmental hygiene and pathogen detection. Emphasis has been made on the importance of effective sanitation practices and advanced detection methods in mitigating healthcare-associated infections based on the results of 10 of our previously published studies on the detection and survival of pathogens on surfaces. Methods: Studies on the detection of pathogens on surfaces are conducted using various phenotype and genotype methods using different databases. For the detection of pathogenic bacteria and fungi on surfaces, several incubation-based methods like contact plates, swabbing, elution, and some other methods can be used. In contrast, genotype methods such as polymerase chain reaction (PCR) offer a rapid alternative to phenotype incubation methods. The detection of viruses is mainly conducted using PCR for gene amplification, followed by virus isolation in cell cultures. Results and Discussion: Hospital surfaces can harbour microorganisms for extended periods, significantly contributing to nosocomial infections. Amidst the COVID-19 pandemic, understanding surface contamination by SARS-CoV-2 became paramount. Implementing rigorous sanitation measures and continuous hygiene monitoring, including regular employee education on hand hygiene are crucial in preventing recontamination. Hospital laundries are potential hotspots for pathogen transmission if textiles are not properly disinfected and handled. Microorganisms can survive on surfaces for various periods at different temperatures. Traditional methods for assessing surface cleanliness, involving surface sampling and classical incubation, are time-consuming methods that may take 2-4 days to analyse the results. Conclusion: This chapter emphasizes the critical need for robust environmental hygiene protocols, advanced detection methods, and continuous monitoring to mitigate the risk of HCAIs. Implementing stringent sanitation measures, educating healthcare workers, and utilizing sensitive detection technologies are some of the essential strategies for the ongoing battle against healthcare-associated pathogens.